Clinical efficacy and safety of laparoscopic nerve-sparing radical hysterectomy for locally advanced cervical cancer. (January 2016) - Liu, Zhongyu; Li, Xiuli; Tao, Ye; Li, Weiping; Yang, Yizhuo; Yao, Yuanqing; Zhu, Tongyu
Abstract: Objective: To evaluate the feasibility and safety of laparoscopic nerve-sparing radical hysterectomy (LNRH) for locally advanced cervical cancer (LACC) after neoadjuvant chemotherapy (NACT). Methods: 120 patients with stage Ib2 and IIa2 cervical cancer were treated with surgery combined with preoperative NACT in the Department of Obstetrics and Gynecology, PLA General Hospital. Eligible patients were divided into two groups according to surgery type: patients who underwent LNRH were assigned to one group, while the second group included patients who underwent laparoscopic radical hysterectomy (LRH) after administration of NACT. We compared these patients' general clinical information and surgical characteristics, and we assessed their bladder function and intestinal function recovery by questionnaire. Results: No significant differences were found between the groups in patients' age or surgical characteristics. The mean duration of postoperative catheterization in the LNRH group was shorter than in the LRH group (P < 0.001). The intestinal and bladder function of patients in the LNRH group also recovered better than that of patients in the LRH group. Conclusion: LNRH is a feasible and safe procedure for LACC after NACT and reduces surgical complications. Highlights: Evaluation of the feasibility and safety in the laparoscopic nerve-sparing radical hysterectomy. Laparoscopic nerve-sparing radical hysterectomy is a minimally invasive surgery procedure for Locally Advanced Cervical Cancer. Laparoscopic nerve-sparing radical hysterectomy is a feasible surgical approach to reduce the occoure rate of surgical complications.